Novel Betanucleorhabdoviruses Infecting Elderberry (Sambucus nigra L.): Genome Characterization and Genetic Variability - Šafářová, Dana; Candresse, Thierry; Veselská, Jana; Navrátil, Milan (Pathogens, 2024)
The genus Betanucleorhabdovirus includes plant viruses with negative sense, non-segmented, single-stranded RNA genomes. Here, we characterized putative novel betanucleorhabdoviruses infecting a medically important plant, elderberry. Total RNA was purified from the leaves of several plants, ribodepleted and sequenced using the Illumina platform. Sequence data analysis led to the identification of thirteen contigs of approximately 13.5 kb, showing a genome structure (3'-N-P-P3-M-G-L-5') typical of plant rhabdoviruses. The detected isolates showed 69.4 to 98.9% pairwise nucleotide identity and had the highest identity among known viruses (64.7-65.9%) with tomato betanucleorhabdovirus 2. A detailed similarity analysis and a phylogenetic analysis allowed us to discriminate the elderberry isolates into five groups, each meeting the sequence-based ICTV demarcation criterion in the Betanucleorhabdovirus genus (lower than 75% identity for the complete genome). Hence, the detected viruses appear to represent five novel, closely related betanucleorhabdoviruses, tentatively named Sambucus betanucleorhabdovirus 1 to 5.